Optimasi Formula Dan Uji Deskriptif Kuantitatif Minuman Jeli Carica Rendah Kalori - Santi Dwi Astuti; Erminawati Erminawati; Anita Suri; Warsono El Kiyat (AGROINTEK, 2021)
Carica fruit (Carica pubescens, Lenne) which is a unique-typical fruit and well listed as a geographical indication product of Wonosobo region Indonesia has high content of vitamin C and potassium (50-100 mg / 100g; 125 ppm). The basic formula (control) consisted of puree and filtrate carica 22.88%, kappa-carrageenan 0.11%, agar 0.08%, konjak glukomanan 0.11%, citric acid 0.08%, sucrose 15.26% and water up to 100%, respectively. The results showed that: 1) the formula with desirability value 0.91 consisting of puree: filtrate = 10,85: 14,5% and sucrose: low-calorie sugar brand X = 7,13: 1.4% resulted in maximum sensory response (sensory score range 1-9) of preference (score 5.5), in range response of elasticity and sweetness (score 5.9 and 5.4); 2) Compared to control, the optimum formula has higher sensory score of fruity flavor, sour aroma, acid taste, and softness (mouthfeel), while texture (springinss and rigidity), sweetness aroma and taste has no different; 3) The optimum formula has similar in hedonic preference with control; 4) Carica jelly drinks with optimum formula has lower carbohydrate, sugar, and energy values (13.59 and 7.4%wb; 40.52Kcal/100g, respectively) than controls (20.37 and 17.42 % wb; 83,16Kcal/100g, respectively).